Profiling individual differences in undergraduates' epistemological beliefs: gender, domain and grade differences - Hakan, Karatas; Munire, Erden (ELSEVIER SCIENCE BV, 2012)
The purpose of this study was to determine undergraduates' epistemological beliefs in terms of gender, domain and grade differences. The participants of the study were composed of 750 undergraduates studying in different departments. To determine the epistemological beliefs of the participants of the study, data were collected using Epistemological Beliefs Scale, originally developed by Schommer (1990) and Turkish bilingual equivalence, validity and reliability of which carried out by Deryakulu and Buyukozturk, (2002), was used. Analyses of t-test were conducted to determine the epistemological beliefs of undergraduates in terms of their gender, domains and grades. The results reveal that significant differences were found in undergraduates' epistemological beliefs in terms of gender and domain. These findings and implications for educational researchers and the significance of such individual differences in epistemological beliefs were discussed.
Keywords: Epistemological beliefs; undergraduates; gender; domain; grade; SECONDARY-SCHOOL; KNOWLEDGE; STUDENTS; SCIENCE; Education & Educational Research